2017
DOI: 10.1152/ajpregu.00324.2016
|View full text |Cite
|
Sign up to set email alerts
|

Activation of CB1receptors by 2-arachidonoylglycerol attenuates vasoconstriction induced by U46619 and angiotensin II in human and rat pulmonary arteries

Abstract: Recent evidence suggests that endocannabinoids acting via cannabinoid CB receptors may modulate vascular responses of various vasoconstrictors in the rodent systemic vasculature. The aim of the study was to investigate whether endocannabinoids modulate the contractile responses evoked by a thromboxane A analog (U46619), angiotensin II (ANG II), serotonin (5-HT), and phenylephrine, which stimulate distinct G protein-coupled receptors (thromboxane, ANG II type 1, 5-HT, and α-adrenergic receptors) in isolated end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(61 citation statements)
references
References 47 publications
(89 reference statements)
2
57
0
Order By: Relevance
“…However, it was observed that eCBs cause vasodilation via mediators released from the endothelium or via activation of endothelial CB 1 receptors, see also Table . These data support the idea that this mechanism occurs, not just in VSMCs, but also in the endothelium . Taking into account the divergent expression of components of the eCB system (see Table ) and the vascular effects of eCBs (connected with their subsequent metabolism to the vasodilatory or/and vasoconstrictor products), the clear interpretation of the results often turns out to be quite problematic.…”
Section: Introductionsupporting
confidence: 61%
See 4 more Smart Citations
“…However, it was observed that eCBs cause vasodilation via mediators released from the endothelium or via activation of endothelial CB 1 receptors, see also Table . These data support the idea that this mechanism occurs, not just in VSMCs, but also in the endothelium . Taking into account the divergent expression of components of the eCB system (see Table ) and the vascular effects of eCBs (connected with their subsequent metabolism to the vasodilatory or/and vasoconstrictor products), the clear interpretation of the results often turns out to be quite problematic.…”
Section: Introductionsupporting
confidence: 61%
“…The blockade of CB 1 receptors resulted in the enhancement of the Ang II‐induced contraction in rPAs (by AM251), rat uterine artery (by rimonabant), rat and mouse gracilis artery as well as mouse saphenous artery (by O2050). Additionally, in the CB 1 ‐knockout mouse model, the inhibition of CB 1 receptors by O2050 did not enhance the Ang II‐induced vasoconstriction in isolated mouse aortas or saphenous arteries .…”
Section: Angiotensin II and Endocannabinoidsmentioning
confidence: 99%
See 3 more Smart Citations